2020
DOI: 10.2147/tcrm.s240125
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhancement of Adherence to Therapeutic and Lifestyle Recommendations Among Hemodialysis Patients: An Umbrella Review of Interventional Strategies</p>

Abstract: Objective: To systematically retrieve and condense the best possible evidence on the successful interventions that targeted enhancement of therapeutic and lifestyle recommendations adherence in hemodialysis patients (HDPs). Design: An umbrella review of interventional studies. Data Sources: A comprehensive search of the Cochrane Database of Systematic Reviews, Ovid, PubMed, Scopus, EMBASE and Web of science databases to identify relevant publications in 2000-2018 (June) timeframe. Study Selection: Two reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…An umbrella review revealed that various intervention approaches and strategies have been used to improve haemodialysis patients' therapeutic and lifestyle recommendation adherence. Psychoeducational interventions have been found to enhance dietary/intake adherence and perceived QoL (Zhianfar, Nadrian, & Shaghaghi, 2020). Psychoeducation often uses cognitive‐behavioural therapy to improve HRQoL and reduces depression and anxiety among haemodialysis patients (Al Saraireh et al, 2018; Ng et al, 2019; Shirazian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An umbrella review revealed that various intervention approaches and strategies have been used to improve haemodialysis patients' therapeutic and lifestyle recommendation adherence. Psychoeducational interventions have been found to enhance dietary/intake adherence and perceived QoL (Zhianfar, Nadrian, & Shaghaghi, 2020). Psychoeducation often uses cognitive‐behavioural therapy to improve HRQoL and reduces depression and anxiety among haemodialysis patients (Al Saraireh et al, 2018; Ng et al, 2019; Shirazian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Psychoeducation often uses cognitive‐behavioural therapy to improve HRQoL and reduces depression and anxiety among haemodialysis patients (Al Saraireh et al, 2018; Ng et al, 2019; Shirazian et al, 2018). However, most intervention studies are outdated and lack explicit explanations of intervention protocols, content, and theory basis (Zhianfar, Nadrian, & Shaghaghi, 2020). Another systematic review had a few studies that used a randomized controlled trial design (Ekuma et al, 2015) or had weaknesses in their randomized controlled trial such as performance (e.g., blinding) and selection bias (e.g., allocation concealment; Ling et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention design was informed by a comprehensive literature review on ESRD [5,[35][36][37][38], evidence on family-based interventions in different chronic conditions [25,26], the researchers' experience, and the results of interviews with HD patients and family caregivers. In fact, there are few systematic data available regarding individuals and families' educational and supportive needs in ESRD.…”
Section: Interventionmentioning
confidence: 99%
“…Nonadherence to diet and medication in HDPs can have substantial repercussions, including poor health outcomes and increased morbidity and mortality. 4 Health protection is the science and art of modifying one's lifestyle to achieve perfection. It entails activities such as proper eating, frequent exercise, avoiding harmful habits, and enhancing one's performance despite the disease.…”
Section: Introductionmentioning
confidence: 99%